Recent Progress on Wavelength‐Selective Perovskite Photodetectors for Image Sensing. Issue 4 (21st February 2023) - Wu, Wenqiang; Lu, Hui; Han, Xun; Wang, Chunfeng; Xu, Zhangsheng; Han, Su‐Ting; Pan, Caofeng
Abstract: Spectral sensing plays a crucial part in imaging technologies, optical communication, and other fields. However, complicated optical elements, such as prisms, interferometric filters, and diffraction grating, are required for commercial multispectral detectors, which hampers their advance toward miniaturization and integration. In recent years, metal halide perovskites have been emerging for optical‐component‐free wavelength‐selective photodetectors (PDs) because of their continuously tunable bandgap, fascinating optoelectronic properties, and simple preparation processes. In this review, recent advances in wavelength‐selective perovskite PDs, including narrowband PDs, dual‐band PDs, multispectral‐recognizable PDs, and X‐ray PDs, are highlighted, with an emphasis on device structure designs, working mechanisms, and optoelectronic performances. Meanwhile, the applications of wavelength‐selective PDs in image sensing for single‐/dual‐color imaging, full‐color imaging, and X‐ray imaging are introduced. Finally, the remaining challenges and perspectives in this emerging field are presented. Abstract : The wavelength‐selective photodetectors (PDs) have extensive applications in image sensing, medical diagnosis, optical communication, etc. Emerging perovskite‐based wavelength‐selective PDs, including narrowband PDs, dual‐band PDs, multispectral‐recognizable PDs, and X‐ray PDs are introduced. The device structure, working mechanism, and performance are emphasized. The applications in image sensing of single‐/dual‐color imaging, full‐color imaging, and X‐ray imaging are summarized.